2022
DOI: 10.1155/2022/7813921
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Chicken Chorioallantoic Membrane (CAM) during Embryonic Development Provides Functional Insight

Abstract: In oviparous animals, the egg contains all resources required for embryonic development. The chorioallantoic membrane (CAM) is a placenta-like structure produced by the embryo for acid-base balance, respiration, and calcium solubilization from the eggshell for bone mineralization. The CAM is a valuable in vivo model in cancer research for development of drug delivery systems and has been used to study tissue grafts, tumor metastasis, toxicology, angiogenesis, and assessment of bacterial invasion. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 127 publications
(215 reference statements)
1
1
0
Order By: Relevance
“…RT-PCR showed that Ch-MSCs positively expressed CD29, CD44, CD73, CD90, and CD166, but CD34 and CD45 were not detected (Figure 4b), indicating that Ch-MSCs widely expressed Ch-MSC markers. This is consistent with previous reports (Ahmed et al, 2022;González et al, 2015;Koo et al, 2012).…”
Section: Characterization Of Ch-mscssupporting
confidence: 94%
“…RT-PCR showed that Ch-MSCs positively expressed CD29, CD44, CD73, CD90, and CD166, but CD34 and CD45 were not detected (Figure 4b), indicating that Ch-MSCs widely expressed Ch-MSC markers. This is consistent with previous reports (Ahmed et al, 2022;González et al, 2015;Koo et al, 2012).…”
Section: Characterization Of Ch-mscssupporting
confidence: 94%
“…The CAM is a highly vascularized double-membrane structure that is connected to the general circulation of the embryo by two allantoic arteries and one allantoic vein. The CAM is fully differentiated and functional by days 12 and 19, respectively [3,4].…”
Section: Structure and Origin Of The Cammentioning
confidence: 99%
“…Proteomic analysis of the CAM on days 12 and 19 has unveiled an extensive array of proteins related to its physiology. These proteins include those involved in calcium ion transport (ATPases, CaBP, and carbonic anhydrases); gas exchange (annexin, hemoglobin, and tubulin); vascularization processes (collagen, integrins, and laminins); and protective molecules against pathogens (cystatins and serpins) [3]. In terms of angiogenesis, the process is predominantly regulated by growth factors with diverse activities including regulatory, proliferative, and inhibitory functions.…”
Section: Structure and Origin Of The Cammentioning
confidence: 99%
See 1 more Smart Citation
“…The chorioallantoic membrane (CAM) of a chicken egg is considered a unique experimental model that is applied to trails of blood vessels [1]. Numerous advantages, including simplicity of manipulation, adequacy of naked-eye observations, and inexpensiveness, put this model at the top of experimental approaches were utilized during investigations of blood vessel biology [2].…”
Section: Introductionmentioning
confidence: 99%